A Post-Synthetic Modification Approach to Expand MIL-101-NH2 Functionalization - Alain Vigroux; Christian Lherbet; Isabelle Fabing; Marie-Claire Barthélémy; Christophe Laurent; Pascal Hoffmann (Chemistry)
Considering the importance of organic functionalization of MOFs, we here report a simple, tunable and efficient one-step post-modification procedure for introducing amino and carboxylic groups into the mesoporous metal–organic framework Al- and Cr-MIL-101-NH2 based on its reaction with alkyl bromides. This procedure allows also access to polyfunctionalized MIL-101 decorated with both carboxylic and primary amino groups. Other chemical functions, such as alcohols and alkynes, were also successfully introduced by this method.